2017
DOI: 10.1007/s11187-017-9896-0
|View full text |Cite
|
Sign up to set email alerts
|

The performance effect of network and managerial capabilities of entrepreneurial firms

Abstract: Building on the organizational capabilities view, this study explores the impact of network and managerial capabilities on the performance of entrepreneurial firms in the architecture and real estate sector. We apply an extended organizational capabilities model by integrating Porter's value chain model and Grant's hierarchy of organizational capabilities. Starting from differences in entrepreneurial orientation between architecture and real estate development firms, we argue that under higher environmental un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…Additionally, by highlighting the characteristics of BSC that provide innovation efficiency, our research illustrates a highly diffused managerial practice that can offer the necessary conditions for decentralized decision-making managed via formal structures and written plans that support superior ability to innovate (Cosh et al 2012;Srećković 2017).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, by highlighting the characteristics of BSC that provide innovation efficiency, our research illustrates a highly diffused managerial practice that can offer the necessary conditions for decentralized decision-making managed via formal structures and written plans that support superior ability to innovate (Cosh et al 2012;Srećković 2017).…”
Section: Discussionmentioning
confidence: 92%
“…However, in SMEs, the flatter structure, faster communication and greater informality of routines and procedures (Srećković 2017) make it more difficult to identify those attributes of the use of BSC that stimulate the development of exploratory innovations in large firms.…”
Section: Balanced Scorecard: Efficiency Gains and Flexibility Lossesmentioning
confidence: 99%
“…Management skills are particularly difficult to measure as they are fundamentally intangible, and overlap with managerial practices or activities, but not completely (O'Gorman et al 2005). Consequently managerial efficacy, or managerial skills, are often proxied by the use of specific managerial practices (see for instance Haber and Reichel 2007;Srećković 2018), for instance the use or development of management skills, namely the introduction of new business practices for organising work procedures, or new methods of organising work responsibilities and decision making.…”
Section: Measuring the Use Of Skillsmentioning
confidence: 99%
“…Networking capability is positively correlated with business performance [11]. It is also alluded that networking capability improves firm performance [18][19].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Further, a study seeking to determine the networking capability related factors that improved the performance of German, Chinese, and Turkish companies concluded that factors affecting performance varied across countries [18]. On the other hand, it was concluded that in cases of environmental uncertainties, network capability help improve the performance of architectural companies while managerial capability help in the real estate firm's performance [19].…”
Section: Empirical Literaturementioning
confidence: 99%